If f (x) = 3x^2 - 8x + 4 and g(x) = 4x^2 - 7x + 3 , then f(x) + g(x) is [tex]7x^2 - 15x + 7[/tex]
Solution:
Given that f(x) = 3x^2 - 8x + 4 and g(x) = 4x^2 - 7x + 3
To find: f(x) + g(x)
We can add or subtract two functions to create a new function. Just like we can add and subtract numbers, we can add and subtract functions.
f(x) + g(x) can be found by adding f(x) and g(x)
[tex]f(x) + g(x) = 3x^2 - 8x + 4 + 4x^2 - 7x + 3[/tex]
Combing like terms,
[tex]f(x) + g(x) = 3x^2 + 4x^2 -7x - 8x + 3 + 4\\\\f(x) + g(x) = 7x^2 - 15x + 7[/tex]
Thus the required function f(x) + g(x) can be found